Spectroscopic and Chromatographic Analytical Methods for Quantification of Rivaroxaban: Review Article (Journal of Pharma Insights and Research, 2025)
Rivaroxaban, a direct factor Xa inhibitor anticoagulant, requires precise and reliable analytical methods for its quantification in pharmaceutical and biological matrices. This work presents the evolution of analytical techniques developed between 2013 and 2024 for rivaroxaban determination. UV spectrophotometric methods offer simplicity and cost-effectiveness, showing linearity in the range of 2-20 µg/mL with detection wavelengths between 250-270 nm. RP-HPLC methods utilizing C18 columns and acetonitrile-based mobile phases achieve detection limits of 8.3 ng/mL, providing enhanced sensitivity and specificity. HPTLC techniques enable simultaneous analysis of multiple samples with minimal preparation steps. LC-MS/MS methods demonstrate superior sensitivity with detection limits in the picogram range, particularly beneficial for bioanalytical applications. Stability-indicating assays reveal degradation patterns under various stress conditions, essential for quality control and stability monitoring. Recent trends indicate a growing emphasis on green analytical chemistry approaches and quality-by-design principles in method development. These methodologies support quality control processes, bioequivalence studies, and therapeutic drug monitoring of rivaroxaban, ensuring accurate quantification across various matrices and concentration ranges.